Conflict of Norms between UUJN and Notarial Deeds: Implications for the Liability of Retired Notaries - Sulistiawati, Sulistiawati; Sri Darmadi, Nanang (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2026)
The purpose of this research is to determine and analyze the responsibility of Notaries for deeds made after the end of their term of office and to determine and analyze the legal protection for Notaries for deeds made after the end of their term of office. This research method includes normative juridical research with a statutory approach and a conceptual approach. Data collection techniques are carried out by literature studies on legal materials, both primary legal materials, secondary legal materials and tertiary legal materials including non-legal materials. The analysis method in this research uses two interpretations which include systematic interpretation and grammatical interpretation. The results of this study indicate that although Defendant II has retired as a Notary, responsibility for the deeds he made, such as Deeds Number 23 and 24, remains attached based on Article 65 of the UUJN. Legal protection for retired Notaries is realized through preventive and repressive mechanisms, including the principle of presumption of legality, limitation of responsibility on formal and procedural aspects, and the right to defend himself in court. Thus, the legal system provides a balance between enforcing the professional responsibilities of Notaries and protecting their rights, so that legal certainty, justice and benefits for Notaries and interested parties remain guaranteed.